KEBIJAKAN KEPALA MADRASAH DAN GURU UNTUK MEWUJUDKAN KONSEP MERDEKA BELAJAR DI MI MIFTAHUL HUDA LAMONG TAHUN 2022 - Ziara Sufi; ali muchasan; Moh. Naufal (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2022)
The current state of education in Indonesia shows that although various efforts have been made to improve the quality of education, in reality there are still deficiencies in the quality of education. The formulation of the problem in this thesis are: 1) How do the principals and teachers interpret the concept of independent learning at MI Miftahul Huda Lamong?. 2) What are the policies of the head of Madrasah and teachers in realizing the concept of independent learning at MI Miftahul Huda Lamong? The results of this study indicate that the understanding of the madrasa principal and MI Miftahul Huda Lamong teacher about the meaning of the concept of independent learning is still lacking. This is because there has never been a direct socialization, so the concept of independent learning is only limited to knowing at a glance. The head of the madrasa in realizing the concept of independent learning at MI Miftahul Huda Lamong also does not yet have a policy.